ABA‐stimulated SoDOG1 expression is after‐ripening inhibited during early imbibition of germinating Sisymbrium officinale seeds. Issue 4 (26th June 2015) - Carrillo‐Barral, Néstor; Matilla, Angel J.; García‐Ramas, Cristina; Rodríguez‐Gacio, María del Carmen
Abstract : DELAY OF GERMINATION 1 ( AtDOG1 ) was the first gene identified as dormancy‐associated, but its physiological role in germination is far from being understood. Here, an orthologue of AtDOG1 in Sisymbrium officinale ( SoDOG1 ; KM009050) is being reported. Phylogenetically, the SoDOG1 gene is included into the dicotyledonous group together with DOG1 from Arabidopsis thaliana (EF028470), Brassica rapa (AC189537), Lepidium papillosum (JX512183, JX512185) and Lepidium sativum (GQ411192). The SoDOG1 expression peaked at the onset of the silique maturation stage and there was presence of SoDOG1 ‐mRNA in the freshly collected viable dry seed (i.e. AR0). The SoDOG1 transcripts were also found in other organs, such as open and closed flowers and to a lesser degree in roots and stems. We have previously reported in S. officinale seeds in which sensu stricto germination is positively affected by nitrate and both testa and micropylar endosperm ruptures are temporally separated. In dry viable seeds, the SoDOG1 ‐mRNA level in three different after‐ripening (AR) status was AR0 ≈ AR7 (optimal AR) < AR27 (optimal AR was almost lost). The presence of nitrate in the AR0 seed imbibition medium markedly decreased the SoDOG1 expression during sensu stricto germination. However, the nitrate stimulated the SoDOG1 expression during imbibition of AR7 compared to AR0. At the early AR0 seed imbibition (3–6 h), exogenous ABA provoked a very strong stimulation of the SoDOG1 expression. AR inhibits ABA‐induced SoDOG1 expression during early germination and gibberellins (GA) can partially mimic this AR effect. A view on the integration of all found results in the sensu stricto germination of S. officinale was conducted.